Antioxidant and anticholinesterase activities of Ipomoea aquatica Forssk. and Ipomoea reptans Poir / Nur Hanis Syuhada Mohd Rosli - Nur Hanis Syuhada , Mohd Rosli (2019)
Ipomoea is the largest genus from the Convolvulaceae family and known to possess various phytochemical compounds. In this study, the antioxidant and anticholineseterase activities of I. aquatica and I. reptans were investigated. I. aquatica and I. reptans are green leafy vegetables and have been utilized for centuries across cultures in managing diseases including in treating neuronal disease such as Alzheimer’s disease (AD). In AD, improper cognitive function has been linked to irregular neuron transmission such as the aberrant activity of acetylcholinesterase enzyme and oxidative stress. Based on the experiments conducted, both plant extracts showed the presence of alkaloids, terpenoids, phenolic compounds and flavonoids. The DPPH scavenging assay showed the highest activity in I. aquatica leaf in methanolic extract (IA-LM) and I. aquatica stem in methanolic extract (IA-SM), indicating I. aquatica has greater scavenging and hydrogen donating ability compared to I. reptans. There was no correlation (R2 = −0.523, P < 0.05) found between DPPH assay and TPC assay, infering that the phenolic compounds present in both plant extracts did not contribute to the scavenging activity observed. The ferric reducing antioxidant power (FRAP) and ferrous ion, Fe2+ chelating assays showed a correlation with the TPC assay suggesting that the phenolic compounds have iron chelating abilities. However, both assays observed low values in all extract indicating that the phenolic compounds present have low reducing power and metal binding ability. The hydrogen peroxide, H2O2 scavenging assay displayed activities < 60 %. In the anticholinesterase assay, acetylcholinesterase (AChE) inhibitory activity was the highest in the chloroform extracts for both plant species, followed by methanol, distilled water and hexane extracts. A correlation with the TPC assay (R2 = 0.636, P < 0.05) showed that the phenolic compounds present in I. aquatica and I. reptans have anticholinesterase activities. Therefore, it can be deduced that both I. aquatica and I. reptans have significant antioxidant and anticholinesterase activities.